Metal-supported palladium membranes for hydrogen separation. (31st October 2015) - Haydn, M.; Ortner, K.; Franco, T.; Schafbauer, W.; Behrens, A.; Dittmar, B.; Hummel, S.; Sulik, M.; Rüttinger, M.; Venskutonis, A.; Sigl, L. S.
Abstract : The demand for clean and green energy has raised the consumption of hydrogen continuously during the last years. Hydrogen is most economically produced in large scale systems by methane steam reforming followed by pressure swing adsorption (PSA). However, with a rising demand for small-scale production of hydrogen, and as down-scaling to smaller PSA-systems ( < 500 Nm 3 /h H2 ) is not economic, a substantial demand for hydrogen generation using palladium membranes has emerged. Porous tubes made of an oxide dispersion strengthened powder metallurgy Fe-Cr alloy (trade name ITM) constitute the backbone for the thin solid Pd films. The tubes provide mechanical and chemical long-term stability in atmospheres with hydrogen- and carbon-species at operation temperatures up to 600°C. A porous ceramic diffusion barrier layer (DBL) is deposited between the ITM-backbone and the Pd thin-film to avoid Pd diffusion into the Fe-Cr substrate and thereby ensure long-term integrity of the system. The Pd thin-film with a thickness < 10 μm is applied onto the DBL by a proprietary coating technology. This paper describes the production route of a tube/diffusion-barrier-layer/Pd-membrane system, its structure and permeation properties.